Legal Politics of the Existence of Fatwa in Islamic Financial Institutions: Evidence from Indonesia - Heris Suhendar; Oyo Sunaryo Mukhlas; Atang Abd. Hakim (Jurnal Hukum Islam, 2023)
The existence of the DSN-MUI Fatwa cannot be separated from the political situation of Indonesia and the legal politics of the formation of Islamic economic regulations. At the end of Soeharto's presidency, the government began to listen to the aspirations of Muslims to incorporate sharia values into legislation. This research aims to examine the background of the issuance of Fatwa DSN-MUI through a legal political approach, and examine the legal position of Fatwa DSN-MUI in Islamic financial institutions. The type of normative research whose object of study is Fatwa DSN-MUI using statute approach, conceptual approach, and historical approach. Sources of legal and non-legal materials were obtained from literature and documentation studies. The existence of Fatwa DSN-MUI is caused by two factors, namely: First, the existence of regulations that require every Islamic financial institution to carry out its business activities in accordance with the Fatwa DSN-MUI; and Second, the development of product innovation in every Islamic financial institution that requires Fatwa DSN-MUI as norms and operational guidelines that govern it. Therefore, the position of Fatwa DSN-MUI in legal substance is morally and legally binding for all Islamic financial service business actors. The binding of the DSN-MUI Fatwa is due to the existence of orders from the legislation. This is differentiates the Fatwa of DSN-MUI from other religious fatwas.